Poster 140: Shoulder Strengthening and Stabilization Systems – A Viable Option for Early Passive Range of Motion after Arthroscopic Rotator Cuff Repair. Issue 7 (30th July 2022) - Rai, Ajinkya; Kane, Gillian; Fox, Michael; Smith, Clair; Lin, Albert; Drain, Nicholas
Objectives: Post-operative rehabilitation following arthroscopic rotator cuff repair (ARCR) is crucial for optimal outcomes. Early post-operative passive range of motion (PROM) is encouraged by some surgeons to minimize the development of adhesions and subsequent decreased range of motion. Existing literature comparing early and delayed PROM for small and medium size tears has demonstrated equivalent functional outcomes, with early PROM resulting in improved long-term active range of motion (AROM). The specific modality used for early PROM varies and may include manual home exercises, machine-assisted home exercises, or formal physical therapy (PT). In this study, we investigated Shoulder Strengthening and Stabilization Systems (SSS) (Advanced Integrated Motion; Elizur), a home-based machine monitored through telemedicine which allows for passive, active-assisted, and active motion in the early post-operative rehabilitation process. The benefit of SSS predominantly derives from the convenience of performing early PROM at home instead of attending in-person formal physical therapy. The objective of this study was to compare patient reported outcomes (PROs) and perioperative AROM after ARCR between patients who utilized SSS and those who underwent formal PT. We hypothesized that those who use SSS would have equivalent ROM and PROs compared to those who did not use SSS. Methods: A retrospective study comprised of patients undergoing RCR between 2018-2020 was conducted. Cohorts were defined by confirmation of SSS utilization via data provided by Elizur. SSS was started within several days following surgery in lieu of formal PT which started at 6 weeks. This was matched with a control group undergoing ARCR over the same time range, who initiated a formal PT protocol without the SSS machine when it was not available at our institution. The post-operative rehabilitation protocol consisted of PROM/pendulums beginning at 10 days, AROM at 6 weeks, and strengthening at 12 weeks. Data were collected from electronic medical records (EMR), entered into an institutional redcap database (UL1-TR-001857), and institutional review board approval was acquired. Patients undergoing concomitant labral repairs, capsular reconstruction procedures, revision ARCR, or with less than 3 months follow up were excluded. Primary outcome measure was subjective shoulder value (SSV) score. Secondary outcomes included American Shoulder and Elbow Surgeons Shoulder Score (ASES), visual analog scale (VAS), and AROM (forward flexion and external rotation). Baseline characteristics were analyzed with two sample t-tests and chi-square or Fisher's exact test for continuous and categorical variables, respectively. A linear mixed model with fixed effects for cohort, time, and the cohort-time interaction was used to analyze PROs and AROM at various timepoints. Statistical significance was set at p < 0.05. Results: A total of 417 patients (243 SSS; 174 no SSS) with an average follow up of 5.5 months met inclusion criteria. SSS was used for an average of 36.2 days. Baseline characteristics including gender, BMI, nature of injury, time from injury to surgery, and preoperative PROs (SSV, ASES, and VAS) did not differ significantly between cohorts. The cohort without SSS was older at the time of surgery (61.3 years vs. 59.3 years, p=0.03). Linear mixed model analysis revealed no significant differences in AROM at any timepoint (table 1). There was no significant difference between cohorts with respect to SSV, ASES, and VAS at any timepoint (Table 2). Both cohorts had significant increases in each PRO over time, exceeding minimal clinically important difference (MCID) at 6 months post-operatively. Conclusions: The use of SSS demonstrated excellent ROM and patient reported outcomes equivalent to those who initiated formal PT in the early postoperative period. The convenience of a home-based therapy program monitored via telemedicine in lieu of formal PT during the first 6 post-operative weeks may be an attractive option for patients following ARCR. Future studies will elucidate whether there are potential cost saving implications. Table 1. Active Range of Motion Over Time Table 2. Patient Reported Outcomes Over Time